Early Exposure to the Scientific Research Process through Collaboration with Chemistry Faculty and the Science Librarian. Issue 2 (2nd April 2016) - Salisbury, Lutishoor; Mattice, Gwendolyn
ABSTRACT: This article reports on the successes of a collaborative effort between science faculty and a science librarian at the University of Arkansas to help freshman chemistry students increase their information literacy skills and their exposure to science faculty members to the point that it motivated them to pursue scientific research projects early in their university studies. Follow-up study suggests that if students are exposed to different professors' research and their requirements for undergraduate research in their freshman year, they are more likely to be engaged in research. Since attending the course, 40 percent of the survey respondents worked on a research project with a faculty member, and 42 percent of them were working on a research project. Half of the respondents felt that this course helped them in some way to get involved with the project they have worked on or are currently engaged in.